Farmer Behavior and Gastrointestinal Nematodes in Ruminant Livestock—Uptake of Sustainable Control Approaches - Vande Velde, Fiona; Charlier, Johannes; Claerebout, Edwin (Frontiers in Veterinary Science, 2018)
Gastrointestinal nematode (GIN) infections are a common constraint in pasture-based herds and cause a decrease in animal health, productivity and farm profitability. Current control practices to prevent production losses of GIN infections in livestock depend largely on the use of anthelmintic drugs. However, due to the continued use of these drugs over more than three decades, the industry is now increasingly confronted with nematode populations resistant to the available anthelmintics. This emerging anthelmintic resistance (AR) in cattle nematodes emphasizes the need for a change towards more sustainable control approaches that limit, prevent or reverse the development of AR. The uptake of diagnostic methods for sustainable control could enable more informed treatment decisions and reduce excessive anthelmintic use. Different diagnostic and targeted or targeted selective anthelmintic control approaches that slow down the selection pressure for anthelmintic resistance have been developed and evaluated recently. Now it is time to transform these insights into guidelines for sustainable control and communicate them across the farmer community. This article reviews the current uptake of such sustainable practices with a focus on farmer’s socio-psychological factors affecting this uptake. We investigate communication as a possible tool to change current behavior and successfully implement more sustainable anthelmintic treatment strategies.